Prospective cohort study investigating frequency and risk factors for acute pain 1 day after refractive surgery - Anat Galor; Jodi Lapidus; Winston Chamberlain; Elyana Vittoria Tessa Locatelli; Jason Betz; Brooke M Harkness; Maricarmen Perez-Blanco; Steven J Everist; Siting Chen; Richard Stutzman; Afshan Nanji; Sue A Aicher (BMJ Open Ophthalmology)
Background/aims To examine demographic and clinical factors associated with ocular pain 1 day after refractive surgery.Methods Prospective study of individuals undergoing refractive surgery. Participants rated their ocular pain on a 0–10 numerical rating scale (NRS) presurgery and 1 day after surgery. Presurgery, participants completed questionnaires on demographics, comorbidities, medications and dry eye and ocular pain symptoms; and an anaesthetised Schirmer test was performed. Acute ocular pain 1 day after surgery was defined as an NRS score of worst pain since surgery ≥3 and this group was compared with individuals with NRS scores<3.Results 251 individuals underwent refractive surgery (89% laser-assisted in situ keratomileusis, n=222; 11% PRK, n=29). Mean age was 35±8 years (range 19 to 60); 60% (n=150) self-identified as female, 80% (n=203) as White, and 36% (n=89) as Hispanic. Thirteen (5%) individuals reported ocular pain (NRS ≥3) prior to surgery and 67% (n=168) reported ocular pain 1 day after surgery (nine individuals had pain at both time points). Factors that were associated with pain 1 day after surgery included Hispanic ethnicity (adjusted relative risk (aRR) 1.42, 95% CI 1.21 to 1.68, p<0.001) and the presence of eye pain presurgery (aRR 1.10, 95% CI 1.02 to 1.18, p=0.02).Conclusion A majority of individuals report moderate or greater pain within 24 hours of refractive surgery. Hispanic ethnicity and eye pain prior to surgery were associated with self-reported acute postsurgical pain.